Manuscript and Print in the Islamic Tradition - Reese, Scott (Studies in Manuscript Cultures, 2022)
This volume explores and calls into question certain commonly held assumptions about the nature of writing and technological advancement in the Islamic tradition. In particular, it challenges the idea that mechanical print naturally and inevitably displaces handwritten texts as well as the notion that the so-called transition from manuscript to print is unidirectional.